A pinworm's tale: The evolutionary history of Lemuricola (Protenterobius) nycticebi. (April 2019) - Frias, Liesbeth; Hasegawa, Hideo; Stark, Danica J.; Lynn, Milena Salgado; Nathan, Senthilvel KSS.; Chua, Tock H.; Goossens, Benoit; Okamoto, Munehiro; MacIntosh, Andrew J.J.
Abstract: Lemuricola (Protenterobius) nycticebi is the only pinworm species known to infect strepsirrhine primates outside Africa, and the only pinworm species yet described in slow lorises. Here, we provided a detailed morphological comparison of female and male worms, and a first description of fourth-stage larvae collected from free-living slow lorises ( Nycticebus menagensis ) in Sabah, Malaysian Borneo. Using mitochondrial and nuclear markers, we also reconstructed the species' phylogenetic relationship with other pinworms infecting primates. Both morphological and molecular results indicated a distinct association between L. (P.) nycticebi and its host. However, while taxonomy identified this species as a member of the Lemuricola clade and grouped pinworms infecting lemurs and slow lorises together, phylogenetic reconstruction split them, placing L. (P.) nycticebi within the Enterobius clade. Our results suggest that L. (P.) nycticebi may represent a different taxon altogether, and that it is more closely related to pinworm species infecting Old World primates outside Madagascar. Pongobius pongoi (Foitová et al., 2008) n. comb. is also proposed. Graphical abstract: Image 1 Highlights: Pinworms and their primate hosts have a long history of association. L. (P.) nycticebi was recovered from slow lorises in the wild. L. (P.) nycticebi was taxonomy classified within the Lemuricola clade. However, molecular phylogenetics placed it within the Enterobius clade. Taxonomic and molecular identifications should complement species descriptions.